Using action and grounded theory techniques as evidence-based design for an academic advising programme (Journal of Student Affairs in Africa, 2024)
Academic advising, if done effectively, can play a significant role in supporting student retention. However, as a relatively new field in South Africa, there is limited, locally contextualised, research into advising interventions and their effectiveness.  We therefore need evidence-based approaches that will lead to more intentionally structured, and shareable practices that meet the needs of our context.  With this paper we detail a methodology through which we were able design an evidence-based, academic advising programme which, we argue, is both effective and academically rigorous. We show how we used the principles of action research, supported by grounded theory analytical techniques, to develop a programme for students facing exclusion at SAU. We collected feedback in cycles, where the student ‘voice’ from one cycle (n=352),  informed the design of the next cycle. Programme evaluation data (n=122) from a third cycle was used to assess the effectiveness of this approach. The results indicate a positive association of the new capability developed in students, with the designed learning activity. This suggests that the approach was effective. The method we describe has application across a wide variety of student development initiatives and can support effective, intentional design and sharing of such practices.
Keywords: Academic advising; action research; grounded theory analysis; evidence-based intervention design